Brain Metastases from Prostate Cancer: An 11‐Year Analysis in the MRI Era with Emphasis on Imaging Characteristics, Incidence, and Prognosis. Issue 2 (28th December 2012) - Hatzoglou, Vaios; Patel, Gita V.; Morris, Michael J.; Curtis, Kristen; Zhang, Zhigang; Shi, Weiji; Huse, Jason; Rosenblum, Marc; Holodny, Andrei I.; Young, Robert J.
ABSTRACT BACKGROUND AND PURPOSE Brain metastases from prostate cancer are uncommon and their imaging appearance has not been well defined. The main objectives of this study were to evaluate the incidence, MRI characteristics, and prognosis of parenchymal brain metastases originating in prostate cancer. METHODS We retrospectively identified 21 patients with prostate cancer and evidence of brain metastases from 2000 to 2010. We reviewed the initial brain MRI scans and characterized the lesions according to location and appearance on MRI, while also determining patient demography, staging, and survival. RESULTS The incidence of brain metastasis from prostate cancer was .16%. At the time of brain metastasis detection, 95% of the patients had concurrent osseous metastases, 86% lymph node metastases, and 76% liver and/or lung metastases. Brain metastases were multifocal in 71% of patients, hemorrhagic in 33%, diffusion restricted in 19%, and partially cystic/necrotic in 19%. The median overall survival after brain metastasis detection was 2.8 months. CONCLUSIONS Brain metastasis from prostate cancer remains a rare phenomenon that most frequently occurs in the setting of widely disseminated bone and soft tissue disease. Patients with nonadenocarcinoma pathology are more likely to develop brain metastases. The MRI appearance is highly variable and prognosis is poor.